Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1289/isee.2011.00499
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, Myocardial Infarction, and Mortality: Effect Modification by Individual and Area-Level Characteristics

Abstract: Background-While several studies have examined associations between temperature and cardiovascular-disease-related mortality, fewer have investigated the association between temperature and the development of acute myocardial infarction (MI). Moreover, little is known about who is most susceptible to the effects of temperature. Methods-We analyzed data from the Worcester Heart Attack Study, a community-wide investigation of acute MI in residents of the Worcester (MA) metropolitan area. We used a casecrossover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 24 publications
5
42
1
Order By: Relevance
“…30 Large increases and decreases in ambient temperature have also been shown to cause increases in the risk of MI. 31 During the 2 weeks following Sandy, the average temperature was around 2.5°C lower than the mean temperature from the same periods in the previous 5 years. 32 For comparison, Madrigano et al found that a 1-day decrease in temperature of 6.6°C was associated with an 8% to 15% increased risk of MI.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…30 Large increases and decreases in ambient temperature have also been shown to cause increases in the risk of MI. 31 During the 2 weeks following Sandy, the average temperature was around 2.5°C lower than the mean temperature from the same periods in the previous 5 years. 32 For comparison, Madrigano et al found that a 1-day decrease in temperature of 6.6°C was associated with an 8% to 15% increased risk of MI.…”
Section: Discussionmentioning
confidence: 84%
“…32 For comparison, Madrigano et al found that a 1-day decrease in temperature of 6.6°C was associated with an 8% to 15% increased risk of MI. 31 Many researchers have found an association between increases in air pollution and higher risk of MI incidence. [33][34][35] We examined the levels of ambient fine particulate pollution, PM2.5, in NJ during our study periods utilizing US Environmental Protections Agency data.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some evidence for other health conditions. Previous case‐crossover studies have shown that exposure to lower temperatures increases the risk of myocardial infarction (), whereas higher temperatures and lower pressures lead to an increase in risk of headaches ().…”
Section: Discussionmentioning
confidence: 99%
“…Chapter 11 writes that "the impacts on health of more frequent heat extremes greatly outweigh benefits of fewer cold days", citing two studies Mills, 2013, Kinney et al, 2012) that only consider cold deaths. Chapter 11 does not cite studies that consider both (Åström et al, 2013, Bell, 2013, Błazejczyk et al, 2013, Chen et al, 2013, El-Fadel and Ghanimeh, 2013, Guo et al, 2013, Madrigano et al, 2013, Oudin Åström et al, 2013, Shaposhnikov et al, 2013, Zanobetti et al, 2013. These studies, published while Chapter 11 was being written, show a more nuanced story (Deschenes, 2014): In some parts of the world, the reduction in cold-related mortality outweighs the increase in heat-related mortality; in other parts of the world, it is the other way around.…”
Section: Human Healthmentioning
confidence: 99%